EVALUASI IMPLEMENTASI PENDIDIKAN KARAKTER PADA ANAK USIA DINI DI MASA PANDEMI COVID-19 - Anim Purwanto (AWLADY : Jurnal Pendidikan Anak, 2022)
This study aims to evaluate of the planning, implementation, and outcome of student character education during the pandemic Covid-19 at PG-TK Al Muslim, Bekasi Regency. The evaluation model was used by Countenance Stake, there are: Introduction, process, and output. Data collection techniques through observation, interviews, and documentation. Source triangulation was used to check and validate the data. The results of evaluation indicate that character education from early needs to be instilled in the golden age, so it is very importan to instill good behavior by applying of character values such as greeting, speaking politely, eating and drinking etiquette, responsibility, and toilet training. Based on the result of evaluation, it is recommended that the character education program be implemented with notes: Improve of planning, methods and learning media, implementation of character education, and outcome of student achievement through character education values.